2022
DOI: 10.1021/acs.jafc.2c03011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidosqualene Cyclases Involved in the Biosynthesis of Diverse Triterpenes in Camellia sasanqua

Abstract: Camellia sasanqua is an important economic plant that is rich in lipophilic triterpenols with pharmacological activities including antiallergic, anti-inflammatory, and anticancer activities. However, the key enzymes related to triterpene biosynthesis have seldom been studied in C. sasanqua. Oxidosqualene cyclases (OSCs) are the rate-limiting enzymes related to triterpene biosynthesis. In this study, seven putative OSC genes (CsOSC1-7) were mined from the C. sasanqua transcriptome. Six CsOSCs were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
(77 reference statements)
2
13
0
Order By: Relevance
“…Likewise, CsOSC6 was identified as a multifunctional α-amyrin synthase, producing β-amyrin (1), α-amyrin (2), and an unknown lanostane derivative (4) at a ratio of 33:64:3 (Figures 2D, S3 and Table S4). CsOSC8 showed activity resembling a known cycloartenol synthase (UXE43252) from C. sasanqua 23 (Figures 2E and S4), in agreement with their phylogenetic grouping.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Likewise, CsOSC6 was identified as a multifunctional α-amyrin synthase, producing β-amyrin (1), α-amyrin (2), and an unknown lanostane derivative (4) at a ratio of 33:64:3 (Figures 2D, S3 and Table S4). CsOSC8 showed activity resembling a known cycloartenol synthase (UXE43252) from C. sasanqua 23 (Figures 2E and S4), in agreement with their phylogenetic grouping.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…CsOSC7 and CsOSC8 are grouped alongside known cycloartenol synthases. It is interesting to note that CsOSCs showed a high degree of similarity with OSC proteins from C. sasanqua, 23 a phylogenetically related species to C. sinensis. Given the substantial evolutionary relatedness of OSC enzymes across plant lineages, a high degree of sequence conservation among these enzymes would be indicative of functional similarities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 19 ] revealed that this compound was β‐amyrin. It was detected in C. japonica stem bark; [ 17 ] C. sinensis leaf; [ 18,20 ] C. tenuifolia seed oil; [ 21 ] in the flowers and stem of C. sativa ; [ 22 ] in the roots, leaves and stem of C. sasanqua ; [ 23 ] in the fruits of C. chekiangoleosa , C. polyodonta , C. semiserrata and C. reticulata . [ 24 ] Furthermore, β‐amyrin was splited for the first time from C. chrysantha .…”
Section: Resultsmentioning
confidence: 99%